2011
DOI: 10.1111/j.1755-3768.2010.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of eye amputated patients

Abstract: ABSTRACT.Purpose: To evaluate eye-amputated patients' health-related quality of life, perceived stress, self-rated health, job separation because of illness or disability and socioeconomic position. Methods: Patients were recruited from a tertiary referral centre situated in Copenhagen. Inclusion criteria were eye amputation, i.e. evisceration, enucleation, orbital exenteration or secondary implantation of an orbital implant during the period 1996-2003, and participation in a previous investigation (2005). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 33 publications
2
35
1
17
Order By: Relevance
“…14,15 However, currently there are no reports on the study of quality of life of children after enucleation.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, currently there are no reports on the study of quality of life of children after enucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of stress and depression, higher separation and divorce rates are reported in enucleated patients compared to the general population. 13,17,20 Although many of the patients in our series found post-operative pain and dissatisfaction with cosmetic appearance to be of concern in the early postoperative period, the vast majority reported overall improvement in these areas compared to their presurgical state. Intolerance of the conformer or prosthesis was reported by 33% of our patients following surgery.…”
Section: Impact Of Treatmentmentioning
confidence: 87%
“…The use of visual analogue scales (VAS) in health research is controversial, 11 but has been suggested as a reliable indicator of global quality of life, including in ophthalmic conditions. 12,13 In our patients, this measure is likely to represent the patients' 'global view' of vision, and take into account any perceived difficulty with reading, peripheral vision and other visuallydependent tasks.…”
Section: Visual Functionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8] In addition, the patient is at risk for psychological and social issues related to the initial diagnosis and postoperative cosmesis. 2,3,9,10 As surgical techniques have evolved, the ability to excise previously inoperable lesions from the face and skull base using a multidisciplinary approach have allowed for local disease control and relatively high survival rates in a limited number of studies. 3 However, such aggressive resections have also resulted in significant craniofacial defects that often extend into the paranasal sinuses and leave large areas of exposed dura and brain ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%